Direito e literatura: a compreensão do direito como escritura a partir da tragédia grega - Costa, César Vergara de Almeida Martins (Universidade do Vale do Rio do Sinos, 2008)
The main objective of the present dissertation is the affirmation of the Law as “scripture”, which is, at same time, transgressor and conservative of the juridical tradition. In order to state so, one has to approach the Law to the Literature, more precisely investigating the relations that have been established between the Greek tragedy and the Law. This way, one has to investigate the general panorama in which the studies that approximate law and literature (and vice-versa) are inserted, and the Aristotelic poetics is visited in order to allow the gender and the tragic man characteristics to be examined. Basic concepts of the ancient Grece are herewith investigated – such as physis, ethos, nomos, hamartia, hybris, themis e diké – as well as the passage of the pre-law structures to the law itself which are unveiled in the Greek myths and, consequently, in the tragic gender based on studies signed by Louis Gernet and Vernant. Identified since the Aristotelic poetics, the mimesis inserted into Literature, and
Keywords: Aristóteles; diké; escritura; ethos; hamartia; hybris; interpretação; literatura; mimesis; nomos; physis; poética; themis; tragédia grega; pré-direito; Aristotle; greek tragedy; interpretation; literature; mímesis; poetics; scripture; pre-law; Ciências Sociais Aplicadas